August Strindberg - Szalczer, Eszter (Routledge modern and contemporary dramatists., 2011)
Dramatist, theatre practitioner, novelist, and painter, August Strindberg's diverse dramatic output embodied the modernist sensibility. He was above all one of the most radical innovators of Western theatre. This book provides an insightful assessment of Strindberg's vital contribution to the dramatic arts, while placing his creative process and experimental approach within a wider cultural context. Eszter Szalczer explores Strindberg's re-definition of drama as a fluid, constantly evolving form that profoundly influenced playwriting and theatrical production from the German Expressio.